THE USE OF THE READING AND THE WRITING LIKE STRATEGY TO TEACH THE HYGIENE IN THE COLOMBIAN SCHOOL AT THE BEGINNING OF THE 20TH CENTURY - Tulio Alfonso Ramírez, Doris Lilia Torres Cruz, (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
The purpose of this paper is to shown the impact it had thought hygienist school in Colombia in the early twentieth century in the teaching of reading and writing. The research is documentary, which is supported in the search for primary sources in the archives of the Ministry of National Education, the National Library of Colombia, the Fund and Fund Teaching in Pedagogical and Technological University of Colombia, the Memoirs of Ministry of Education in 1903-1930, the Official Gazette, located in the Archives of the Department of Boyacá. This document offers the possibility of recognizing the impact of external factors on the teaching of reading and writing, as significant elements in the development of reading process that took Colombia to the early twentieth century. While literacy was promoted utilitarian and practical purposes, which contributed to the management of technology, manufacturing industry and agriculture, also was in the service of thought that promoted hygienist and splendor of the language. Identifying reading and writing as tools other than the condition of the subject itself, generates the impossibility of raising critical processes, and meaningful participation in a process of nation building.